FARM TRACTOR MECHATRONIC STEERING MODULE - Linenko, Andrey V.; Gabitov, Ildar I.; Siraev, Shamil F.; Aznagulov, Aynur I.; Lukyanov, Valerij V.; Kamalov, Timur I. (Journal of Applied Engineering Science, 2019)
This paper proposes a mechatronic steering module consisting of two parts which allows you to increase the speed of the automatic control system, simplify the design and reduce its cost. In the electromechanical part of the mechatronic module a brushless DC motor is used, its rotor being an integral part of the steering wheel. To change the position of the rotor is to turn the steering wheel without intermediate mechanisms. To implement the software and hardware, a mathematical model was developed. On the basis of this model an algorithm was obtained that describes the movement pattern of a tractor with an agricultural machine. The mechatronic module was tested in comparison with the gear thruster on the MTZ 82.1 tractor. The two systems testing showed that the mechatronic module did not obstruct the view and did not hinder the farm tractor steering. The advantage of the proposed module is the ability to quickly switch to manual control, whereas with the gear thruster, it takes time to manually retract the gear between the electric motor and the steering shaft. To install the electromechanical part of the mechatronic module takes half the time compared to the gear thruster, and the farm tractor movement accuracy is 17% higher. This is due to the fact that the “reaction time” of the mechatronic module does not exceed 0.25 seconds. The cost of the developed mechatronic module is 240 thousand rubles, which is comparable to that of the gear thruster.
Keywords: Mechatronic module; Navigation; Precision agriculture; tractor